La consommation énergétique à Calcutta (Inde) : du confort thermique aux statuts sociaux - Margot Pellegrino (VertigO)
This article aims at studying a practice of high energy fallout: the increasing use of air conditioning in public and private Indians spaces. To answer the question "Is air conditioning necessary ?", we studied the link between technical measure and subjective perception of thermal comfort, and between energy consumption and social practices, for a specific case study in Calcutta. The methodology lies at the intersection of technical and social approaches. The study shows how a physical objective data, in this case the temperature, can imply variable subjective perceptions. The study also shows that the relationship between subjective perception (thermal comfort) and energy practices (use of air conditioners) is not linear. The results of this study finally allow understanding that the energy behaviour of a part of the studied sample is determined by a social aspiration. This aspiration consists in demonstrating, through the possession of an object (the air-conditioner) and the modality of its use (detached from a real necessity), the right to belong to a specific and identifiable social status. Thus, the definition of thermal comfort itself has to integrate social analysis: thermal comfort not only depends on a subjective response to physical environmental data, but it is also determined by representations that are specific to each social class.